2017
DOI: 10.1161/jaha.117.007268
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of the Effects of Insulin and Metformin on Myocardial Injury and Stress in Diabetes Mellitus: A Post Hoc Exploratory Analysis

Abstract: BackgroundSubclinical myocardial injury, as measured by high‐sensitivity cardiac troponin T (hsTnT), and myocardial stress, as measured by N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP), are related to glycemic control in patients with type 2 diabetes mellitus, and are strong predictors of adverse cardiovascular outcomes. We sought to determine whether antihyperglycemic therapy improves measures of myocardial injury and myocardial stress in patients with type 2 diabetes mellitus.Methods and ResultsWe ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
(80 reference statements)
1
1
0
Order By: Relevance
“…Thorough statistical analysis of hs-cTnI and hs-cTnT levels in the HOME cohort, which previously reported reduced macrovascular disease risk as a result of metformin treatment, did not reveal evidence of a clinically relevant effect of metformin treatment on these cardiac biomarkers, when compared with placebo. Our results corroborate and extend previously published work by Srivastava et al which investigated short-term effects of metformin on circulation concentrations of cardiac troponin T, reporting no significant effect in a population of relatively recent-onset diabetes [ 19 ]. The authors hypothesized that long-term glucose control might lead to reduction in troponin T that was not observed within their 12 week setting.…”
Section: Discussionsupporting
confidence: 93%
“…Thorough statistical analysis of hs-cTnI and hs-cTnT levels in the HOME cohort, which previously reported reduced macrovascular disease risk as a result of metformin treatment, did not reveal evidence of a clinically relevant effect of metformin treatment on these cardiac biomarkers, when compared with placebo. Our results corroborate and extend previously published work by Srivastava et al which investigated short-term effects of metformin on circulation concentrations of cardiac troponin T, reporting no significant effect in a population of relatively recent-onset diabetes [ 19 ]. The authors hypothesized that long-term glucose control might lead to reduction in troponin T that was not observed within their 12 week setting.…”
Section: Discussionsupporting
confidence: 93%
“…In recent years, disorders of glucose and lipid metabolism have gradually become global epidemic diseases, mainly including hyperlipidemia, diabetes, and other diseases, and seriously threatening human health [ 1 ]. Some researchers have found that disorders of glucose and lipid metabolism are caused by a variety of factors, such as the abnormal metabolic processes of glucose and lipid synthesis and decomposition and absorption in the body, which lead to excess lipids, insulin resistance, and liver damage [ 2 ].…”
Section: Introductionmentioning
confidence: 99%